Involute-Evolute D-Curves in Minkowski 3-Space E13 - Almaz, Fatma; Kulahci, Mihriban Alyamac (Soc Paranaense Matematica, 2021)
In this paper, we examine the notion of the involute-evolute curves for the curves lying the surfaces in Minkowski 3-space E-1(3). We call these new associated curves as involute-evolute and by using the Darboux frame of the curves. We give the representation formulae for spacelike curves in Minkowski 3-space E-1(3) and using this formulae we give some characterizations of these curves. Besides, we find the relations between the normal curvatures, the geodesic curvatures and the geodesic torsions of these curves.
Keywords: Involute-evolute curve; darboux frame; normal curvature; geodesic curvature